Repolarization of inflammatory macrophages into reparative stage targeting cannabinoid receptor2: a potential perspective to dampen lung injury/ARDS - Benedict, Chloe; Joshi, Jagdish Chandra (Frontiers in Pharmacology, 2025)
The inflammatory response during acute lung injury and ARDS leads to an overactive immune response, causing further damage and irreparable recovery. While there are drugs to target various pathogens that cause acute lung diseases, still, the consequences of infection-induced inflammatory signaling and damage prevention are limited with available drugs. With the rise of cannabinoids as a potential therapeutic agent in several inflammatory disease states, many studies have specifically evaluated their anti-inflammatory effects via CB2 receptors and non-cannabinoid receptors, such as GPR18, in infectious lung injury. However, the exact mechanisms behind CB2 receptor agonism in the application of acute lung injury are still not clear. Lung macrophages are major immune cells that play a major role in checking and defending the primary and secondary consequences of lung infectious injury. The exact mechanism by which macrophages differentiate to produce anti-inflammatory effects over inflammation is still widely debated during episodes of acute lung injury or respiratory distress. Using systematic literature evaluation and analysis of current trends and gaps in the literature, we have analyzed the mechanisms that CB2 agonists involve in dampening inflammatory signaling and redirecting the response in acute lung injuries/ARDS by modifying the nature of inflammatory macrophages to anti-inflammatory. Our systematic review indicated that within the inflammatory macrophage response, CB2 agonists impact several signaling pathways involved in the excessive immune response, reducing the expression of inflammatory transcription factors and inflammatory cytokine storm, and redirecting the macrophages to resolve the lung injury/ARDS.